(untitled) (Perner’s Contacts, 2016)
This article deals with video surveillance system for traffic from the perspective of their legal establishment on the basis of specific legal provisions, specific usability and practical knowledge from their operations. On specific situations and cases we notify on miscellaneous safety risks connected with the operation and service of these systems that arise from legal restrictions and risks resulting from breach of these legal obligations - especially in view of the Act on the Protection of Personal Data.